O-GlcNAcylation and chromatin remodeling in mammals: an up-to-date overview. (13th April 2017) - Leturcq, Maïté; Lefebvre, Tony; Vercoutter-Edouart, Anne-Sophie
Abstract : Post-translational modifications of histones and the dynamic DNA methylation cycle are finely regulated by a myriad of chromatin-binding factors and chromatin-modifying enzymes. Epigenetic modifications ensure local changes in the architecture of chromatin, thus controlling in fine the accessibility of the machinery of transcription, replication or DNA repair to the chromatin. Over the past decade, the nutrient-sensor enzyme O -GlcNAc transferase (OGT) has emerged as a modulator of chromatin remodeling. In mammals, OGT acts either directly through dynamic and reversible O-GlcNAcylation of histones and chromatin effectors, or in an indirect manner through its recruitment into chromatin-bound multiprotein complexes. In particular, there is an increasing amount of evidence of a cross-talk between OGT and the DNA dioxygenase ten–eleven translocation proteins that catalyze active DNA demethylation. Conversely, the stability of OGT itself can be controlled by the histone lysine-specific demethylase 2 (LSD2). Finally, a few studies have explored the role of O -GlcNAcase (OGA) in chromatin remodeling. In this review, we summarize the recent findings on the link between OGT, OGA and chromatin regulators in mammalian cellular models, and discuss their relevance in physiological and pathological conditions.